Sistem Informasi Laporan Jasa Pengiriman Barang Pada CV. Mitrajasa Perdana Anugrah Berbasis Web - Diwahana Mutiara Candrasari; Anggi Anggraini (Universitas Ivet, 2020)
Mitrajasa Perdana Anugrah Is the company which are engaged in cargo transport services of the company komanditer located on jl .Raya kober gg .Manggis no 3 ( front of market kober sub-district regency banyumas provincial central java. In running their business cv .Mitrajasa prime gift not using a computer to records the transactions but still use books manually , so as to make data to inefficient , as often happens mistake in writing , the book used could have been exposed to water and make data be unable to read , and often books forget put it even the book missing and causing loss for CV. Mitrajasa Perdana Anugrah, by building information system report cargo transport services web-based in CV. Mitrajasa Perdana Anugrah. Is expected to overcome the problems faced by CV. Mitrajasa Perdana Anugrah. The .Application information system delivery service report is built with a use of language programming php and database management system used is mysql. This application can inform the sender, regarding the data recipients, data delivery, data courier, the sender, report the reports on the recipients, delivery, report courier, report so easier to accessed by the user. Could also see in the report quick application report information system was built cargo transport services web-based that can be accessed easily, fast, and accurate anytime, so to speed up decision-making.